Low-warping-degree copper-clad plate and preparation process thereof
By introducing a low shrinkage curing agent into the copper clad glue solution and optimizing the yarn density of the glass fiber cloth, the problem of warping of the CEM-1 type copper clad substrate is solved, and the preparation of low warpage copper clad plate is realized, which improves the reliability and performance of the product.
Patent Information
- Application Number
- CN202411807833.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The substrate warping problem of CEM-1 type copper clad plate leads to unsmooth PCB process, affecting the insertion and mounting of electronic components, and may lead to contact breakage and increase in scrap rate.
By improving the copper clad liquor, low-shrinkage curing agents, such as polycarboxyl POSS and lipoic acid compounding, combined with appropriate glass fiber cloth yarn density and hot pressing conditions, a low-warping copper clad plate was prepared.
It effectively reduces the warpage of the copper clad plate, reduces the internal stress generated during the curing process, improves mechanical and electronic properties, and reduces the waste rate.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a low-warpage copper-clad laminate and a preparation process thereof. Background Art
[0002] In the modern electronic manufacturing industry, copper clad laminate (CCL) is the basic material of printed circuit board (PCB), and its quality is directly related to the performance and reliability of PCB. In particular, CEM-1 type copper clad laminate has been widely used in multilayer boards and double-sided boards due to its high cost-effectiveness and good mechanical strength. However, the warpage of CEM-1 copper clad laminate (hereinafter referred to as substrate warpage) is a product defect that copper clad laminate factories, printed circuit board factories and related users are extremely concerned about but not easy to solve. It is also a problem of great concern to electronic assembly factories and related users.
[0003] Substrate warping not only affects the smooth progress of the PCB process, such as causing pattern deformation or board jamming on the PCB automatic production line, but also hinders the automatic insertion and placement of electronic components. More seriously, substrate warping may cause the integrated block contact points to not fit tightly with the PCB pads, and the stress caused by warping may also cause the contacts to break, resulting in an increase in the scrap rate. In addition, substrate warping also poses challenges to the installation and use of electronic devices. For example, it is difficult to insert the PCB into the socket, and even if it is successfully inserted, the functionality of the device may be affected due to poor contact.
[0004] In order to solve the problem of substrate warping, the applicant designed a low-warping copper-clad laminate and a preparation process thereof. Summary of the invention
[0005] The object of the present invention is to provide a low-warpage copper-clad laminate and a preparation process thereof, so as to solve the technical problems mentioned in the above background technology.
[0006] The technical solution for achieving the purpose of the present invention is: A low-warpage copper-clad laminate, wherein the low-warpage copper-clad laminate is prepared by firstly completely and evenly impregnating glass fiber cloth with copper-clad laminate glue and then drying to obtain a prepreg; then, stacking a plurality of prepregs with flat surfaces and even coating, attaching copper foils on the upper and lower parts and hot pressing them; the copper-clad laminate glue comprises, by weight, raw material components of: 80-100 parts by weight of epoxy resin, 44-55 parts by weight of a low-shrinkage curing agent, 1.6-2 parts by weight of an accelerator, 10-30 parts by weight of a flame retardant, and 90-110 parts by weight of a solvent.
[0007] Furthermore, the low shrinkage curing agent is obtained by compounding polycarboxyl POSS and lipoic acid.
[0008] Furthermore, the accelerator is accelerator DMP-30.
[0009] Furthermore, the flame retardant is any one of diphenyl toluene ester, trichloropropyl phosphate, DOPO, and hexaphenoxy cyclotriphosphazene.
[0010] Furthermore, the solvent is a mixture of butanone and propylene glycol methyl ether acetate.
[0011] Furthermore, a preparation process of a low warpage copper clad laminate comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 90-110 parts by weight of solvent to the adhesive tank, then add 80-100 parts by weight of epoxy resin and 44-55 parts by weight of low shrinkage curing agent, stir at 70-90 r / min for 2.5-3.5 hours to mix evenly, then add 1.6-2 parts by weight of accelerator and 10-30 parts by weight of flame retardant, stir at a speed of 800-1200 rpm for 5-7 hours, remove bubbles after aging, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in an oven at 115-125°C for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 5~17MPa and a temperature of 160~180℃. Hot press for 90~130min and keep warm for 0.8~1.2h.
[0012] Furthermore, the glass cloth has a warp yarn count density of 38-42 yarns / inch, and a weft yarn count density of 36-40 yarns / inch.
[0013] Furthermore, the low shrinkage curing agent is obtained by mixing polycarboxyl POSS and lipoic acid in a mass ratio of 2-4:1.
[0014] Furthermore, the preparation steps of the polycarboxyl POSS are as follows: 44-46 parts by mass of acrylic acid, 0.4-0.6 parts by mass of cage-type octavinyl silsesquioxane, 4-6 parts by mass of tetrahydrofuran, 0.9-1.1 parts by mass of sodium dodecyl sulfate and 38-42 parts by mass of deionized water are mixed, stirred at 80-90° C. for 55-65 min, 11-13 parts by mass of potassium persulfate are added three times in three equal parts, each addition is separated by 30 min, and the reaction is carried out for 5-7 hours after the addition is completed to obtain the polycarboxyl POSS.
[0015] Furthermore, the preparation steps of the cage-type octavinyl silsesquioxane are as follows: after mixing 400 parts by mass of acetone and 62-64 parts by mass of vinyltrimethoxysilane, 129-131 parts by mass of 37% hydrochloric acid solution and 100-120 parts by mass of deionized water are added at 4-6 drops / s, and after the addition is completed, the mixture is reacted at 30-50° C. for 47-49 hours, cooled, filtered, washed and dried to obtain cage-type octavinyl silsesquioxane.
[0016] By adopting the above technical solution, the present invention has the following beneficial effects: (1) The present invention improves the copper clad laminate adhesive and introduces a low shrinkage curing agent to reduce the curing shrinkage of the epoxy resin, thereby shortening the shrinkage difference between the epoxy resin and the glass cloth and copper foil, thereby reducing the internal stress generated in the product after curing, thereby reducing the warpage of the copper clad laminate.
[0017] (2) The low shrinkage curing agent of the present invention is prepared by compounding polycarboxyl POSS and thioctic acid. By introducing polycarboxyl POSS, the curing agent can add a rigid POSS structure to the copper clad laminate adhesive, thereby toughening and modifying the adhesive, thereby reducing the curing shrinkage of the copper clad laminate adhesive. At the same time, the addition of POSS greatly increases the number of silicon-oxygen bonds and carbon-silicon bonds, effectively reducing the number of polarized molecules per unit volume, and the POSS structure has a cavity characteristic, which effectively reduces the dielectric constant and dielectric loss of the copper clad laminate adhesive. Even if the introduction of thioctic acid inevitably causes volume shrinkage during the curing process, in the subsequent hot pressing step, the dynamic disulfide bonds in the thioctic acid can promote the destruction and rearrangement of the polymer network of the semi-cured sheet, while maintaining the cross-linking density basically unchanged, ensuring that the mechanical properties of the copper clad laminate are not affected, and effectively reducing the stress caused by volume shrinkage, thereby reducing the warping phenomenon of the copper clad laminate.
[0018] (3) Compared with the conventional glass cloth having a warp yarn count of 42 to 46 yarns / inch and a weft yarn count of 32 to 36 yarns / inch, the glass cloth of the present invention has a warp yarn count of 38 to 42 yarns / inch and a weft yarn count of 36 to 40 yarns / inch. The yarn counts per inch in the warp and weft directions are more similar, and the distribution of the adhesive in the glass cloth is more uniform, thereby reducing the problem of inconsistent curing shrinkage caused by the difference in yarn count density. This not only improves the consistency of the curing shrinkage rate of the glass cloth in the radial and weft directions, but also effectively reduces the warping phenomenon of the copper clad laminate during the curing process. DETAILED DESCRIPTION
[0019] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0020] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.
[0021] Some of the raw materials of the embodiments of the present invention and the comparative examples are as follows: The epoxy resin adopts bisphenol A epoxy resin; The flame retardant is toluene diphenyl ester; The solvent is a mixture of butanone and propylene glycol methyl ether acetate in a mass ratio of 11:9; The accelerator used is accelerator DMP-30.
[0022] (Example 1) A preparation process for a low-warpage copper-clad laminate comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 90 parts by weight of solvent into the adhesive tank, then add 80 parts by weight of epoxy resin and 44 parts by weight of low shrinkage curing agent, stir at 70 r / min for 2.5 h to mix evenly, then add 1.6 parts by weight of accelerator and 10 parts by weight of flame retardant, stir at 800 rpm for 5 h, remove bubbles after aging, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in an oven at 115°C for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 5 MPa and a temperature of 160°C. Press for 90 minutes and keep warm for 0.8 hours.
[0023] The glass cloth has a warp yarn count density of 38 yarns / inch and a weft yarn count density of 36 yarns / inch.
[0024] The low shrinkage curing agent is obtained by mixing polycarboxyl POSS and thioctic acid in a mass ratio of 2:1.
[0025] The preparation steps of the polycarboxyl POSS are as follows: 44 parts by mass of acrylic acid, 0.4 parts by mass of cage-type octavinyl silsesquioxane, 4 parts by mass of tetrahydrofuran, 0.9 parts by mass of sodium dodecyl sulfate and 38 parts by mass of deionized water are mixed, stirred at 80° C. for 55 minutes, 11 parts by mass of potassium persulfate are added in three equal parts three times, each addition is separated by 30 minutes, and the reaction is carried out for 5 hours after the addition is completed to obtain the polycarboxyl POSS.
[0026] The preparation steps of the cage-type octavinyl silsesquioxane are as follows: 400 parts by mass of acetone and 62 parts by mass of vinyltrimethoxysilane are mixed, and 129 parts by mass of 37% hydrochloric acid solution and 100 parts by mass of deionized water are added at a rate of 4 drops / s, and after the addition is completed, the mixture is reacted at 30° C. for 47 hours, cooled, filtered, washed, and dried to obtain the cage-type octavinyl silsesquioxane.
[0027] (Example 2) A preparation process for a low-warpage copper-clad laminate comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 100 parts by weight of solvent into the adhesive tank, then add 90 parts by weight of epoxy resin and 50 parts by weight of low shrinkage curing agent, stir at 80 r / min for 3 h to mix evenly, then add 1.8 parts by weight of accelerator and 20 parts by weight of flame retardant, stir at a speed of 1000 rpm for 6 h, remove bubbles after aging, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in a 120°C oven for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 11 MPa and a temperature of 170°C. Press for 110 minutes and keep warm for 1 hour.
[0028] The glass cloth has a warp yarn count density of 40 yarns / inch and a weft yarn count density of 38 yarns / inch.
[0029] The low shrinkage curing agent is obtained by mixing polycarboxyl POSS and thioctic acid in a mass ratio of 3:1.
[0030] The preparation steps of the polycarboxyl POSS are as follows: 45 parts by mass of acrylic acid, 0.5 parts by mass of cage-type octavinyl silsesquioxane, 5 parts by mass of tetrahydrofuran, 1 part by mass of sodium dodecyl sulfate and 40 parts by mass of deionized water are mixed, stirred at 85° C. for 60 minutes, 12 parts by mass of potassium persulfate are added in three equal parts, each addition is separated by 30 minutes, and the reaction is carried out for 6 hours after the addition is completed to obtain the polycarboxyl POSS.
[0031] The preparation steps of the cage-type octavinyl silsesquioxane are as follows: 400 parts by mass of acetone and 63 parts by mass of vinyltrimethoxysilane are mixed, and 130 parts by mass of 37% hydrochloric acid solution and 110 parts by mass of deionized water are added at a rate of 5 drops / s, and after the addition is completed, the mixture is reacted at 40° C. for 48 hours, cooled, filtered, washed, and dried to obtain the cage-type octavinyl silsesquioxane.
[0032] (Example 3) A preparation process for a low-warpage copper-clad laminate comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 110 parts by weight of solvent to the adhesive tank, then add 100 parts by weight of epoxy resin and 55 parts by weight of low shrinkage curing agent, stir at 90 r / min for 3.5 h to mix evenly, then add 2 parts by weight of accelerator and 30 parts by weight of flame retardant, stir at 1200 rpm for 7 h, remove bubbles after aging, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in a 125°C oven for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 17 MPa and a temperature of 180°C. Hot press for 130 minutes and keep warm for 1.2 hours.
[0033] The glass cloth has a warp yarn count density of 42 yarns / inch and a weft yarn count density of 40 yarns / inch.
[0034] The low shrinkage curing agent is obtained by mixing polycarboxyl POSS and lipoic acid in a mass ratio of 4:1.
[0035] The preparation steps of the polycarboxyl POSS are as follows: 46 parts by mass of acrylic acid, 0.6 parts by mass of cage-type octavinyl silsesquioxane, 6 parts by mass of tetrahydrofuran, 1.1 parts by mass of sodium dodecyl sulfate and 42 parts by mass of deionized water are mixed, stirred at 90° C. for 65 minutes, 13 parts by mass of potassium persulfate are added in three equal parts three times, each addition is separated by 30 minutes, and the reaction is carried out for 7 hours after the addition is completed to obtain the polycarboxyl POSS.
[0036] The preparation steps of the cage-type octavinyl silsesquioxane are as follows: 400 parts by mass of acetone and 64 parts by mass of vinyltrimethoxysilane are mixed, and 131 parts by mass of 37% hydrochloric acid solution and 120 parts by mass of deionized water are added at a rate of 6 drops / s, and after the addition is completed, the mixture is reacted at 50° C. for 49 hours, and then cooled, filtered, washed, and dried to obtain the cage-type octavinyl silsesquioxane.
[0037] (Comparative Example 1) A preparation process for a low-warpage copper-clad laminate comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 100 parts by weight of solvent into the adhesive tank, then add 90 parts by weight of epoxy resin and 50 parts by weight of low shrinkage curing agent, stir at 80 r / min for 3 h to mix evenly, then add 1.8 parts by weight of accelerator and 20 parts by weight of flame retardant, stir at a speed of 1000 rpm for 6 h, remove bubbles after aging, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in a 120°C oven for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 11 MPa and a temperature of 170°C. Press for 110 minutes and keep warm for 1 hour.
[0038] The glass cloth has a warp yarn count density of 40 yarns / inch and a weft yarn count density of 38 yarns / inch.
[0039] The low shrinkage curing agent only uses polycarboxyl POSS.
[0040] The preparation steps of the polycarboxyl POSS are as follows: 45 parts by mass of acrylic acid, 0.5 parts by mass of cage-type octavinyl silsesquioxane, 5 parts by mass of tetrahydrofuran, 1 part by mass of sodium dodecyl sulfate and 40 parts by mass of deionized water are mixed, stirred at 85° C. for 60 minutes, 12 parts by mass of potassium persulfate are added in three equal parts, each addition is separated by 30 minutes, and the reaction is carried out for 6 hours after the addition is completed to obtain the polycarboxyl POSS.
[0041] The preparation steps of the cage-type octavinyl silsesquioxane are as follows: 400 parts by mass of acetone and 63 parts by mass of vinyltrimethoxysilane are mixed, and 130 parts by mass of 37% hydrochloric acid solution and 110 parts by mass of deionized water are added at a rate of 5 drops / s, and after the addition is completed, the mixture is reacted at 40° C. for 48 hours, cooled, filtered, washed, and dried to obtain the cage-type octavinyl silsesquioxane.
[0042] (Comparative Example 2) A preparation process for a low-warpage copper-clad laminate comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 100 parts by weight of solvent into the adhesive tank, then add 90 parts by weight of epoxy resin and 50 parts by weight of low shrinkage curing agent, stir at 80 r / min for 3 h to mix evenly, then add 1.8 parts by weight of accelerator and 20 parts by weight of flame retardant, stir at a speed of 1000 rpm for 6 h, remove bubbles after aging, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in a 120°C oven for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 11 MPa and a temperature of 170°C. Press for 110 minutes and keep warm for 1 hour.
[0043] The glass cloth has a warp yarn count density of 40 yarns / inch and a weft yarn count density of 38 yarns / inch.
[0044] The low shrinkage curing agent is obtained by mixing maleic anhydride and thioctic acid in a mass ratio of 3:1.
[0045] (Comparative Example 3) A preparation process for a low-warpage copper-clad laminate comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 100 parts by mass of solvent to the adhesive tank, then add 90 parts by mass of epoxy resin and 50 parts by mass of curing agent, stir at 80 r / min for 3 h to mix evenly, then add 1.8 parts by mass of accelerator and 20 parts by mass of flame retardant, stir at a speed of 1000 rpm for 6 h, remove bubbles after aging, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in a 120°C oven for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 11 MPa and a temperature of 170°C. Press for 110 minutes and keep warm for 1 hour.
[0046] The glass cloth has a warp yarn count density of 40 yarns / inch and a weft yarn count density of 38 yarns / inch.
[0047] The curing agent is maleic anhydride.
[0048] (Comparative Example 4) A preparation process for a low-warpage copper-clad laminate comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 100 parts by weight of solvent into the adhesive tank, then add 90 parts by weight of epoxy resin and 50 parts by weight of low shrinkage curing agent, stir at 80 r / min for 3 h to mix evenly, then add 1.8 parts by weight of accelerator and 20 parts by weight of flame retardant, stir at a speed of 1000 rpm for 6 h, remove bubbles after aging, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in a 120°C oven for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 11 MPa and a temperature of 170°C. Press for 110 minutes and keep warm for 1 hour.
[0049] The glass cloth has a warp yarn count density of 44 yarns / inch and a weft yarn count density of 34 yarns / inch.
[0050] The low shrinkage curing agent is obtained by mixing polycarboxyl POSS and thioctic acid in a mass ratio of 3:1.
[0051] The preparation steps of the polycarboxyl POSS are as follows: 45 parts by mass of acrylic acid, 0.5 parts by mass of cage-type octavinyl silsesquioxane, 5 parts by mass of tetrahydrofuran, 1 part by mass of sodium dodecyl sulfate and 40 parts by mass of deionized water are mixed, stirred at 85° C. for 60 minutes, 12 parts by mass of potassium persulfate are added in three equal parts, each addition is separated by 30 minutes, and the reaction is carried out for 6 hours after the addition is completed to obtain the polycarboxyl POSS.
[0052] The preparation steps of the cage-type octavinyl silsesquioxane are as follows: 400 parts by mass of acetone and 63 parts by mass of vinyltrimethoxysilane are mixed, and 130 parts by mass of 37% hydrochloric acid solution and 110 parts by mass of deionized water are added at a rate of 5 drops / s, and after the addition is completed, the mixture is reacted at 40° C. for 48 hours, cooled, filtered, washed, and dried to obtain the cage-type octavinyl silsesquioxane.
[0053] (Comparative Example 5) A preparation process for a low-warpage copper-clad laminate comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 100 parts by mass of solvent to the adhesive tank, then add 90 parts by mass of epoxy resin and 50 parts by mass of curing agent, stir at 80 r / min for 3 h to mix evenly, then add 1.8 parts by mass of accelerator and 20 parts by mass of flame retardant, stir at a speed of 1000 rpm for 6 h, remove bubbles after aging, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in a 120°C oven for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 11 MPa and a temperature of 170°C. Press for 110 minutes and keep warm for 1 hour.
[0054] The glass cloth has a warp yarn count density of 44 yarns / inch and a weft yarn count density of 34 yarns / inch.
[0055] The curing agent is maleic anhydride.
[0056] Effect example Warpage: The low-warpage copper-clad laminates prepared in the examples and comparative examples were tested for warpage according to JIS C 6481 standard.
[0057] Dielectric constant and dielectric loss factor: The low warpage copper clad laminates prepared in the examples and comparative examples were measured for dielectric constant and dielectric loss factor at 10 GHz using the flat plate method according to IPC-TM-6502.5.5.9.
[0058] Toughness: Use an impact tester with a drop height of 45cm and a drop weight of 1kg. Good or bad toughness evaluation: A clear cross indicates better toughness of the product, indicated by character ①; a blurred cross indicates poor toughness and high brittleness of the product, indicated by character ②; a cross with a clarity between clear and blurred indicates average toughness of the product, indicated by character ③.
[0059] Table 1 below shows the performance test data of the low warpage copper clad laminates prepared in the examples and comparative examples: Table 1
[0060] As shown in Table 1, the dielectric constant and dielectric loss of the low-warpage copper-clad laminates prepared in Examples 1 to 3 are low, the warpage is low, and the toughness is good; the difference between Comparative Example 1 and Example 2 is that the low shrinkage curing agent of Comparative Example 1 only uses polycarboxyl POSS, and the dielectric constant, dielectric loss, warpage, and toughness of Comparative Example 1 and Example 2 are compared, and the warpage of Example 2 is low; the difference between Comparative Example 2 and Example 2 is that the low shrinkage curing agent of Comparative Example 2 is obtained by mixing maleic anhydride and thioctic acid in a mass ratio of 3: 1, and the dielectric constant, dielectric loss, warpage, and toughness of Comparative Example 2 are compared with those of Example 2, and the dielectric constant, dielectric loss, warpage, and toughness of Example 2 are low, the warpage is low, and the toughness is good; the difference between Comparative Example 3 and Example 2 is that the curing agent of Comparative Example 3 only uses maleic anhydride, and Comparative Example 3 and Compared with the dielectric constant, dielectric loss, warpage and toughness of Example 2, the dielectric constant and dielectric loss of Example 2 are lower, the warpage is lower and the toughness is better; the difference between Comparative Example 4 and Example 2 is that the warp yarn count density of the glass cloth in Comparative Example 4 is 44 yarns / inch, and the weft yarn count density is 34 yarns / inch. Compared with the dielectric constant, dielectric loss, warpage and toughness of Example 2, the warpage of Example 2 is lower; the difference between Comparative Example 5 and Example 2 is that the curing agent of Comparative Example 5 only uses maleic anhydride, and the warp yarn count density of the glass cloth is 44 yarns / inch, and the weft yarn count density is 34 yarns / inch. Compared with the dielectric constant, dielectric loss, warpage and toughness of Example 2, the dielectric constant, dielectric loss, warpage and toughness of Example 2 are lower, the dielectric constant, dielectric loss, warpage and toughness of Example 2 are lower.
[0061] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A low-warpage copper-clad laminate, wherein the low-warpage copper-clad laminate is obtained by firstly completely and evenly impregnating glass fiber cloth with copper-clad laminate glue and then drying it to obtain a prepreg; then, a plurality of prepregs with flat surfaces and even coating are stacked, and copper foils are attached to the upper and lower parts and hot-pressed; characterized in that: The copper clad laminate adhesive comprises, by weight, 80 to 100 parts by weight of epoxy resin, 44 to 55 parts by weight of a low shrinkage curing agent, 1.6 to 2 parts by weight of an accelerator, 10 to 30 parts by weight of a flame retardant, and 90 to 110 parts by weight of a solvent.
2. The low warpage copper clad laminate according to claim 1, characterized in that: The low shrinkage curing agent is prepared by compounding polycarboxyl POSS and lipoic acid.
3. The low warpage copper clad laminate according to claim 1, characterized in that: The accelerator used is accelerator DMP-30.
4. The low warpage copper clad laminate according to claim 1, characterized in that: The flame retardant is any one of diphenyl ester of toluene, trichloropropyl phosphate, DOPO, and hexaphenoxy cyclotriphosphazene.
5. The low warpage copper clad laminate according to claim 1, characterized in that: The solvent is a mixture of butanone and propylene glycol methyl ether acetate.
6. A process for preparing a low warpage copper clad laminate, characterized in that: The method comprises the following preparation steps: (1) Preparation of copper clad laminate adhesive: After cleaning the adhesive tank, add 90-110 parts by weight of solvent to the adhesive tank, then add 80-100 parts by weight of epoxy resin and 44-55 parts by weight of low shrinkage curing agent, stir at 70-90 r / min for 2.5-3.5 hours to mix evenly, then add 1.6-2 parts by weight of accelerator and 10-30 parts by weight of flame retardant, stir at a speed of 800-1200 rpm for 5-7 hours, remove bubbles, and obtain copper clad laminate adhesive; (2) Preparation of prepreg: The glass fiber cloth is completely and evenly soaked with the copper clad laminate glue and then placed in an oven at 115-125°C for baking to obtain a prepreg. The glue content is controlled to be about 45% and the fluidity is about 30%; (3) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, and place them in a vacuum hot press with a pressure of 5~17MPa and a temperature of 160~180℃. Hot press for 90~130min and keep warm for 0.8~1.2h.
7. The process for preparing a low warpage copper clad laminate according to claim 6, characterized in that: The glass cloth has a warp yarn count density of 38-42 yarns / inch, and a weft yarn count density of 36-40 yarns / inch.
8. The process for preparing a low warpage copper clad laminate according to claim 6, characterized in that: The low shrinkage curing agent is obtained by mixing polycarboxyl POSS and thioctic acid in a mass ratio of 2-4:
1.
9. The process for preparing a low warpage copper clad laminate according to claim 8, characterized in that: The preparation steps of the polycarboxyl POSS are as follows: 44-46 parts by weight of acrylic acid, 0.4-0.6 parts by weight of cage-type octavinyl silsesquioxane, 4-6 parts by weight of tetrahydrofuran, 0.9-1.1 parts by weight of sodium dodecyl sulfate and 38-42 parts by weight of deionized water are mixed, stirred at 80-90° C. for 55-65 minutes, 11-13 parts by weight of potassium persulfate are added three times in three equal parts, each addition is separated by 30 minutes, and the reaction is performed for 5-7 hours after the addition is completed to obtain the polycarboxyl POSS.
10. The process for preparing a low warpage copper clad laminate according to claim 9, characterized in that: The preparation steps of the cage-type octavinyl silsesquioxane are as follows: 400 parts by mass of acetone and 62-64 parts by mass of vinyltrimethoxysilane are mixed, and 129-131 parts by mass of 37% hydrochloric acid solution and 100-120 parts by mass of deionized water are added at a rate of 4-6 drops / s, and after the addition is completed, the mixture is reacted at 30-50° C. for 47-49 hours, and then cooled, filtered, washed, and dried to obtain the cage-type octavinyl silsesquioxane.
Citation Information
Patent Citations
Variable-stiffness self-repairing material containing metal-sulfydryl coordinate bond as well as preparation and application thereof
CN113817173A
High-heat-dissipation low-dielectric copper-clad plate and preparation method thereof
CN116552074A
Hydraulic pressure intensifier
KR102542921B1
Composite material, high-frequency circuit substrate made therefrom and making method thereof
US20110045304A1
High-frequency resin prepolymer, and high-frequency resin composition, prepreg, laminated board, and interlayer insulating film prepared by using same
WO2020143336A1